REPOSISI PERAN DAN FUNGSI PEREMPUAN - Arbaiyah Prantiasih (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2014)
Women empowerment effort is an integral part of national development. Therefore, women empowerment effort is an on-going attempt in accordance to the dynamics of rapid economic and social culture changes in this modern era. The targets of women empowerment are to develop women’s potentials which enable them to take the benefit of their right and opportunities the same as men do; and to use their right and potentials the same as men do on development resources. In this way, women can develop their own capacity for actulizing their roles as men’s equals partners for family and state development. Due to the equal duties and obligations in facing global challenge, women must play their domestic and public roles equally